Penggunaan Fasilitas E-Banking Dalam Minat Nasabah Studi Kasus Pada PT. BRI Syariah Kantor Cabang Pembantu Stabat - Asmawarna Sinaga, Anjur Perkasa Alam, Faisal Efendi, Fajar Siddiq (Journal Economy and Currency Study (JECS), 2021)
This study proposes a qualitative analysis of the use of E-Banking Facilities in the Interests of Customers. Case Study at PT. BRI Syariah Stabat Sub-Branch Office with a focus on the problem, namely what are the e-banking channels available at PT. BRI Syariah Stabat Sub-Branch Office, what are the benefits for customers using the e-banking channel facilities available at PT. BRI Syariah Stabat Sub-Branch Office, and what are the obstacles in e-banking channel services found at PT. BRI Syariah Stabat Sub-Branch Office. This type of research is a field research (field research) which is a case study using a descriptive qualitative approach and the process of inferring research results by inductive thinking, the method used is a qualitative method, namely a research strategy that uses more and collects in-depth information on the phenomenon being studied. researched. This analysis is carried out by examining and examining in depth the data obtained, in order to obtain conclusions that can be accounted for in scientific studies. Based on the results of research in the field, it is known that the Electronic Banking channels at PT. BRI Syariah Stabat Sub-Branch Offices are BRIS e-banking, smsBRIS, mobile BRIS, CMS BRIS (Cash Management System), BRIS e-form and BRIS Laku Pandai. The advantages received by customers in using BRIS e-banking are banking transaction service facilities through the internet network that can be accessed for 24 hours, BRIS SMS makes it easy for customers to top up credit, pay bills, transfers to pay Zakat, Infaq and Shodaqah, Mobile BRIS allows Customers obtain banking information using their cellphones, the BRIS CMS (Cash Management System) facilitates electronic services that provide services in the form of customer financial transactions, the BRIS e-form makes it easy to open a Faedah Savings account at BRI sharia through online, Laku Pandai BRIS facilitates banking and/or services other financial services that are carried out not through office networks, but through collaboration with other parties and need to be supported by the use of information technology facilities. The obstacles that occur to customers in the use of Electronic Banking facilities at PT. BRISyariah Stabat Sub-Branch Office, namely the customer's ability to use technology due to the lack of public knowledge about e-banking facilities and the sometimes unsupportive network also makes it difficult for customers in some areas to access networks such as in rural areas, causing customers to still choose transact by visiting the branch office